SER PROFESSOR NO SÉCULO XXI: AS REPRESENTAÇÕES SOCIAIS DE ALUNOS INGRESSANTES E CONCLUINTES DE UM CURSO DE PEDAGOGIA - Mayara Aparecida Pereira Menezes; Augusta Boa Sorte O. Klebis; Raimunda Abou Gebran (Universidade do Oeste Paulista, 2016)
he present paper reports a study that sought to bring to the debate the role of social representations in the construction of teacher identity and how the initial training can contribute to the strengthening of this process towards a professionalism that meets the current challenges of teaching. Thus, we aimed to carry out a reflection on the social representations of students, from the first and the final period of the Pedagogy graduating course, on what is to be a teacher, in the current context, and its relation to the construction of teacher's identity. More specifically, it sought to: a) compare the social representations among students entering and graduating in Pedagogy; b) analyze the influence of cultural, social and political-educational context in the construction of these representations; c) reflect upon the establishment of a dialogue between the social representations of students and the quality of initial training offered by the institution. We have chosen a qualitative approach of field research, which was based on the Social Representations Theory (SRT), developed by Moscovici (2015), as well as the structural approach of representations - Central Nucleus Theory (CNT)-, proposed by Abric (1994). The data were collected through a questionnaire and the Test WordsAssociation Test - WAT. The analysis of the data obtained in the field research allows us to conclude that the Pedagogy course has a significant influence on the constitution of the teacher identity. Thus, it is also configured as a space for construction and reconstruction of social representations, which tends to reflect positively in the course of future profession.